THE IMPACT OF INTERNATIONAL TOURIST ARRIVALS ON ECONOMIC GROWTH UNDER DENGUE FEVER RISK IN MALAYSIA (Journal of Economics and Sustainability, 2022)
Dengue fever has long been a community health problem in tropical countries. Dengue virus is a crucial cause of disease in international tourists, with a rising number of them returning from dengue‐endemic countries infected with dengue fever. This study analyses the impact of international tourist arrivals on economic growth moderated by dengue fever cases in Malaysia from 2014 until 2020. This study was carried out using secondary monthly data for dengue fever cases, gross domestic product (GDP), and international tourist arrivals. A correlation test was used to analyse the correlation between the independent, dependent and moderating variables. Granger causality test was employed to determine the causality between the selected three variables, dengue fever cases, international tourist arrivals, and economic growth. The results reveal a significant correlation between dengue fever cases, tourist arrivals, and economic growth. Between 2017 and 2018, higher international tourist arrivals led to lower economic growth under dengue disease hazards in Malaysia. Furthermore, dengue fever risk is found to have a positive relationship with international tourist arrivals and vice versa. The findings show a causality effect between the selected variables. The selected three indicators drive each other in the period study. In line with the government’s strategy to promote the Malaysian tourism industry, prevention and recovery policies should be planned considering the number of dengue cases and economic factors.